Pengaruh Penerapan Sistem E-Filing dan Peran Account Representative Terhadap Kepatuhan Wajib Pajak Orang Pribadi Yang Terdaftar Pada KPP Pratama Pekanbaru Senapelan - Shabrina, Wahyu; Siti Samsiah; Evi Marlina (Akuntansi dan Manajemen, 2024)
This study aims to determine the effect of the implementation of the e-filing system and the role of account representatives on Individual Taxpayer Compliance Study at KPP Pratama Pekanbaru Senapelan. This research is a quantitative research. The sampling method is carried out using a simple random sampling technique. This study used primary data, namely from the distribution of questionnaires distributed directly by field researchers. This research was conducted on Individual Taxpayers registered at the Pekanbaru Senapel Pratama Tax Service Office. The population in this study is Individual Taxpayers who report Annual Returns (SPT) at KPP Pratama Pekanbaru Senapelan amounting to 35,402 people with a sample of 100 individual taxpayers. The data analysis used was multiple linear regression analysis using SPSS v.26. Based on the results of the data processing, it can be concluded that the application of the e-filing system and the role of the account representative affect the compliance of individual taxpayers. The implication of this study is that it refers to the application of the e-filing system and the role of account representatives on WPOP compliance to research informants supported by taxpayer data that reports Annual Tax Returns at KPP Pratama Pekanbaru Senapelan. It is expected that WPOP will further improve tax return reporting in accordance with tax laws and regulations through the E-filing system and the Tax Service Office provides good understanding and services through the role of Account Representative.